Biodegradation of used motor oil in soil using organic waste amendments - Abioye, O.P.; Agamuthu, Pariatamby; Abdul Raman, Abdul Aziz (Hindawi Publishing Corporation, 2012)
Soil and surface water contamination by used lubricating oil is a common occurrence in most developing countries. This has been shown to have harmful effects on the environment and human beings at large. Bioremediation can be an alternative green technology for remediation of such hydrocarbon-contaminated soil. Bioremediation of soil contaminated with 5 and 15 (w/w) used lubricating oil and amended with 10 brewery spent grain (BSG), banana skin (BS), and spent mushroom compost (SMC) was studied for a period of 84 days, under laboratory condition. At the end of 84 days, the highest percentage of oil biodegradation (92) was recorded in soil contaminated with 5 used lubricating oil and amended with BSG, while only 55 of oil biodegradation was recorded in soil contaminated with 15 used lubricating oil and amended with BSG. Results of first-order kinetic model to determine the rate of biodegradation of used lubricating oil revealed that soil amended with BSG recorded the highest rate of oil biodegradation (0.4361 day(-1)) in 5 oil pollution, while BS amended soil recorded the highest rate of oil biodegradation (0.0556 day(-1)) in 15 oil pollution. The results of this study demonstrated the potential of BSG as a good substrate for enhanced remediation of hydrocarbon contaminated soil at low pollution concentration.